Penerapan “SGMS” Industri Kosmetik di Indonesia dalam Kajian Ethics - Nurul Mardhiah Sitio; Jovanica Putri Wardi (International Forum of Researchers and Lecturers, 2025)
Business is an integrated part of a country's economic development, the development of the cosmetic industry that increases annually as people's awareness of skin health triggers companies to meet the need for cosmetic products and body care. Increased cosmetic production has led to worsening environmental conditions as a result of the use of natural resources and waste pollution. The impact of the industry demands companies to increase accountability in environmental management. With the application of green management system, ministers not only are profitably oriented but are also promoting a management system that can provide guidance for companies to remain environmentally sound. One of the companies that has been implementing green management is the body shop.